Survei Jentik Aedes Sp, Pengetahuan dan Perilaku 3M Plus Masyarakat di Provinsi Jawa Barat - Erna Veronika; Meithyra Melviana Simatupang; Ahmad Irfandi; Mayumi Nitami (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background of Study: Dengue hemorrhagic fever is caused by the dengue virus which is carried by the Aedes sp mosquito as a vector. Environmental conditions and community behaviour are the factors that influence the spread of this infection. Therefore, the efforts to control DHF in the community are carried out with the movement to eradicate mosquito nests through the 3M Plus program. In 2020, West Java Province recorded the highest cases of DHF in Indonesia, so it was catagorized as red zone and became the dengue endemic area. This study aimed to describe the presence larvae of Aedes sp, the community's knowledge dan behaviour about 3M Plus in West Java ProvinceMethods: This descriptive study used a cross sectional design, conducted in West Java Province in 2020. The sample of this study as many as 136 households and was selected using purposive sampling technique.Results: The results showed that 77.2% of the community's knowledge level of 3M plus was catagorized as good, 51.5% of the people implemented 3M Plus, and no mosquito larvae were found in 72.8% of the respondents' housesConclusion: The majority of the community had good knowledge and had implemented the 3M Plus program with results showing that in most of the community's homes no larvae were found. It is suggested to the community to regularly monitor larvae around their homes.Keywords: Dengue fever; Larva survey; 3M plus; Water container